Tough Life after Prison: An Analysis of 19 Former Prisoners in Malaysia - Jasni, Mohd Alif; Abu Bakar Ah, Siti Hajar; Che Mohd Nasir, Norruzeyati (Journal of Community Development Research (Humanities and Social Sciences), 2020)
Undeniably, some former prisoners have succeeded in reintegrating themselves back into society and have also ceased any further criminal activities. However, this journey is difficult for former prisoners, particularly when their families do not welcome their return or when they fail to secure a steady job. This study was conducted to understand the challenges and obstacles faced by former prisoners during reintegration process using protective factor as an indicator. A qualitative approach was adopted in this study, whereby 19 former prisoners were interviewed to enhance the understanding of this issue. Based on the findings obtained, it was revealed that only three respondents met the characteristics of a person who had successfully desisted from committing a crime. This finding proved that desistance from crime among former prisoners is challenging. Thus, the criminal justice system in Malaysia towards the reintegration of former prisoners should be improved accordingly to prevent any failure or potential issue for the betterment of former prisoners. The recommendation of this study is to introduce a community-based post-release program as a social intervention in Malaysia criminal justice system. The limitation of this study is in the discussion done only from the perspective of former prisoners. There is a need to conduct studies from the perspective of social workers, counsellors and volunteers in the NGOs involved in helping former prisoners throughout the process of reintegration. Keywords : Desistance, Recidivism, Former Prisoner, Reintegration, Risk Factor, The Protective Factor